Quantitative identification of different single molecules by selective time-resolved confocal fluorescence spectroscopy - Fries, JR; Brand, L; Eggeling, C; Kollner, M; Seidel, C (1998)
Using a confocal epi-illuminated microscope together with a pulsed laser, new applications of the recently developed, real-time spectroscopic technique BIFL (burst integrated fluorescence lifetime) are introduced. BIFL registers two different types of information on every detected photon with regard to the macroscopic time scale of a measurement and to the fluorescence lifetime. Thus, it is shown to be well suited to identify freely diffusing single dye molecules via their characteristic fluorescence lifetime. This allows for selective counting of dye molecules in an open volume element and opens up the possibility to quantify the relative concentration of the dye molecules, using a recently derived theoretical model, which analyzes the obtained burst size distribution of a sample survey. A closed theory is presented to calculate the probability of a specific dye to cause a fluorescence burst containing a certain number of detected photons. It considers the distribution of the excitation irradiance over the detection volume together with saturation effects of the fluorescence and of the detection electronics, the probability of different transit times through the detection volume, and the probability of multimolecule events. Using BIFL together with selective counting, the concentration of two dyes, Rhodamine B and Rhodamine 6G, in separate solutions and in a mixture were determined. The obtained results are consistent with the applied dye concentrations and with simultaneous measurements by fluorescence correlation spectroscopy (FCS). The introduced method is an appropriate tool for the complete characterization and quantitative analysis of a highly diluted sample in homogeneous assays.